System with display and advisory on payment technology preference through modern networking - Tsok, Jia Xuan (2025)
In the modern evolving digital economy, businesses are facing increasing pressure to accommodate multiple wireless payment methods—such as digital wallets, credit cards, and cryptocurrencies—within their current enterprise infrastructure. However, the lack of integration among these systems typically results in business inefficiencies, security vulnerabilities, and siloed customer experiences. The purpose of this project is to address these problems by establishing a single, unified platform that integrates the wireless payment solutions into the Odoo Enterprise Resource Planning (ERP) system. The solution uses Stripe for processing digital wallet transactions and CoinGate for cryptocurrency payment processes, respectively, with real-time synchronization with critical business modules like sales, inventory, and accounting. A user-friendly dashboard has been developed that displays transactions and provides strategic payment recommendations using business intelligence (BI) approach. The system design, which is driven by Odoo's modular framework, offers secure payments, automation, and expandability to allow for future enhancements. By providing backend automation along with advisory visualization, the system provides enhanced financial intelligence, reduces errors, and encourages informed decision-making. Not only does this project ease payment management, but it also facilitates the greater good of establishing secure, smart, and efficient digital payment ecosystems for next-generation businesses.